Perencanaan Strategis Sistem Informasi Pembelajaran dengan Metode Balanced Scorecard - Latjuba Sofyana STT; Brillian Jalu Fatwa (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2021)
The development of digital technology has driven transformation in the education sector, including the implementation of e-learning-based information systems. The success of such systems requires a well-directed strategic plan to ensure effectiveness, efficiency, and alignment with the goals of educational institutions. This study aims to design a strategic plan for e-learning information systems using the Balanced Scorecard (BSC) approach, integrating four main perspectives: financial, customer, internal processes, and learning and growth. The research methodology involves needs analysis, identification of key performance indicators (KPIs), and the development of BSC-based strategies to optimize e-learning implementation. The findings reveal that implementing the BSC approach can enhance resource allocation efficiency, user satisfaction, and the quality of learning processes. The financial perspective emphasizes efficient budget management, while the customer perspective ensures system accessibility and usability for students, teachers, and parents. The internal process perspective focuses on efficient workflow management, and the learning and growth perspective supports user competency development and the adoption of new technologies. (Arifani & Darmawan, 2016)This study also concludes that developing applications such as a Learning Management System (LMS), academic management applications, and school management applications is essential. Furthermore, technological infrastructure requirements, including administrative computers, servers, and Wi-Fi access, are critical elements for supporting successful e-learning implementation. The BSC-based strategic approach proves effective in helping educational institutions design and manage learning information systems sustainably in the digital era. .